THE EFFECTIVENESS OF VISUAL, AUDITORY, KINESTHETIC (VAK) MODEL IN TEACHING WRITING ON PROCEDURE TEXT FOR THE SEVENTH GRADE STUDENTS AT SMP MUHAMMADIYAH 2 TARAKAN - Permatasari, Dian; Ridwan, Ridwan; Almustaqim, Taqwim (Universitas Borneo Tarakan, 2022)
The objective of the research was to investigate whether there was any significant difference between the students who were taught by using Visual, Auditory, Kinesthetic (VAK) model and those who were taught by using Mind Mapping model in teaching writing on procedure text for the seventh-grade students at SMP Muhammadiyah 2 Tarakan. The method used in this research was quasi-experimental, and the design of this research was a nonequivalent group design. The sample of this research was class VII A as the experimental class and VII C as the control class by using a purposive sampling technique. The research instrument was a writing test. The Independent Sample of T-test was used to analyze the data. The result of this research showed that there was a significant difference between the students who were taught by using Visual, Auditory, Kinesthetic (VAK) model and those who were taught by using Mind Mapping model in writing procedure text. It was proven by the result of the students’ mean score in the pretest and posttest. The students’ mean score in the pretest in the experiment class was 32.83 and the students’ mean score in the pretest in the control class was 36.83. The students’ mean score in the posttest in the experiment class was 55.83 and the students’ mean score in the posttest in the control class was 46.50. The students’ mean score in the posttest in the experiment class was higher than that of the control class. The result of the Independent sample of T-test obtained tcount = 2.095 and ttable with df = N- 2 = 46 at the level of significance 5% or 0.05 was 2.013. It can be concluded that tcount ttable was 2.095 2.013. Then, there was a significant effect of the implementation of Visual, Auditory, Kinesthetic (VAK) model in teaching writing on procedure text for the seventh-grade students at SMP Muhammadiyah 2 Tarakan.